Wildlife of Australia - Campbell, Iain (Princeton University Press, 2013)
Ideal for the nature-loving traveler, Wildlife of Australia is a handy photographic pocket guide to the most widely seen birds, mammals, reptiles, amphibians, and habitats of Australia. The guide features more than 400 stunning color photographs, and coverage includes 350 birds, 70 mammals, 30 reptiles, and 16 frogs likely to be encountered in Australia's major tourist destinations. Accessible species accounts are useful for both general travelers and serious naturalists, and the invaluable habitat section describes the Australian bush and its specific wildlife. Animal species with similar features are placed on the same plates in order to aid identification. Wildlife of Australia is an indispensable and thorough resource for any nature enthusiast interested in this remarkable continent. Easy-to-use pocket guide More than 400 high-quality photographs Accessible text aids identification Habitat guide describes the Australian bush and its specific wildlife Coverage includes the 350 birds, 70 mammals, 30 reptiles, and 16 frogs most likely to be seen on a trip around Australia
Description based on online resource; title from PDF title page (publisher's Web site, viewed Mar. 30, 2016)
Keywords: Vertebrates -- Australia -- Identification; Tiere; Australien; Bestimmungsbuch